Perspectives on Parallel Computing. - Deng, Yuefan; Glimm, James; Sharp, David H. (Daedalus: Journal of the American Academy of Arts & Sciences)
Discusses how parallel computing and computers are removing mental tasks from human minds and increasing the amount and complexity of mental tasks that are undertaken. Impact on science; Parallel computing in the future; Factors that limit the scale of parallelism; Limited programmability; More.